2018
DOI: 10.1002/ccr3.1822
|View full text |Cite
|
Sign up to set email alerts
|

Superior semicircular canal dehiscence with concomitant otosclerosis—A literature review and case discussion

Abstract: Key Clinical MassageComputed tomography scan should be performed as a routine before every stapes surgery, in order to exclude concomitant superior semicircular canal dehiscence, since no other clinical, audiological, or electro‐physiological criteria are available to exclude concomitant superior semicircular canal dehiscence in the otosclerotic temporal bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Although the coexistence of otosclerosis and SSCD or SSCND findings is rarely seen in the literature, it has been reported that the underlying pathogeneses are different and it is coincidental that they are found simultaneously in the same patient [ 7 , 8 ]. The prevalence of concomitant otosclerosis and SSCD findings has been reported to be 6 to 8 per 100,000 [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the coexistence of otosclerosis and SSCD or SSCND findings is rarely seen in the literature, it has been reported that the underlying pathogeneses are different and it is coincidental that they are found simultaneously in the same patient [ 7 , 8 ]. The prevalence of concomitant otosclerosis and SSCD findings has been reported to be 6 to 8 per 100,000 [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the coexistence of otosclerosis and SSCD or SSCND findings is rarely seen in the literature, it has been reported that the underlying pathogeneses are different and it is coincidental that they are found simultaneously in the same patient [ 7 , 8 ]. The prevalence of concomitant otosclerosis and SSCD findings has been reported to be 6 to 8 per 100,000 [ 8 ]. It is known that there may be congenital or acquired causes in the development of SSCD, but congenital causes are prominent, and familial cases of SSCD syndrome have been reported [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cases in which otosclerosis and SSCD occur simultaneously, the preoperative radiological diagnosis of both conditions can also be beneficial, as this particular situation increases the risk of unsatisfactory surgical outcomes. 44 The presence of diverticula from the internal auditory canal (IAC), usually in the anteroinferior wall, (►Fig. 7) is more frequently observed in individuals with otosclerosis.…”
Section: Computed Tomography Findings As Predictors Of Intraoperativementioning
confidence: 99%
“…Although SCDS cannot exist without SCD, the presence of a radiographic dehiscence may simply be apparent because of inadequate slice thickness or visualization in the proper planes to give a false impression of a dehiscence when in fact a thin plate of bone remains intact. Even some patients with a true bony dehiscence may remain asymptomatic (2). Furthermore, SCDS, the physiologically active clinical syndrome caused by the bony dehiscence, can present anywhere from a mild nuisance to debilitating symptoms.…”
mentioning
confidence: 99%
“…When the question of an active dehiscence arises, we agree that vestibular-evoked myogenic potential (VEMP) testing may be useful; however, results can be difficult to interpret because of unpredictable stimulation of the third window due to the effect of otosclerosis (2). As expected, air conduction VEMPs may be absent in more than 75% of cases because of inefficient transmission of acoustic energy to the inner ear, whereas even bone conduction VEMPs may be absent in nearly a quarter of patients with otosclerosis, more so for those with a greater degree of hearing loss (3).…”
mentioning
confidence: 99%